Atorvastatin Combining with Probucol: A New Way to Reduce Serum Uric Acid Level during Perioperative Period of Interventional Procedure - Hong Li; Ximing Li; Hongjun Ma; Yiran Wang; Naikuan Fu; Dongxia Jin; Hongliang Cong (The Scientific World Journal)
Uric acid has ever been considered as one of contrast induced acute kidney injury’s risk factors. Atorvastatin and probucol can both improve contrast induced acute kidney injury separately. This prospective study is to assess their effect on reducing serum uric acid level and contrast induced acute kidney injury during perioperative period of interventional procedure. On the basis of different doses of atorvastatin and probucol, 208 cases admitted for coronary angiography or percutaneous coronary intervention were randomly classified into standard combined group (S-C group), intensive combined group (I-C group), and intensive atorvastatin group (I-A group). Patients’ blood urea nitrogen, serum creatinine, and serum uric acid were measured and estimated glomerular filtration rate was evaluated 24 hours before and after the procedure. After procedure, blood urea nitrogen in all the three groups decreased; Scr of S-C group and I-A group increased significantly, while estimated glomerular filtration decreased in the S-C group (P<0.05); serum uric acid in S-C group and I-C group decreased significantly (P<0.05). Combination treatment of atorvastatin and probucol before intervention could reduce perioperative serum uric acid level; meanwhile, the intensive combined treatment can improve the contrast induced acute kidney injury. The result was the same for hypertensive patients.